2022
DOI: 10.1111/eea.13205
|View full text |Cite
|
Sign up to set email alerts
|

Hexanal combined with decanal mediate host location by the bamboo powderpost beetle, Dinoderus minutus

Abstract: The bamboo powderpost beetle, Dinoderus minutus (Fabricius) (Coleoptera: Bostrichidae), is the major post-harvest pest of several bamboo species worldwide.Conspecific adults colonize injured bamboo stems, primarily those with low moisture content. Here, the volatiles from dry cut stems of Bambusa vulgaris Schrad. ex J.C. Wendl (Poaceae) were identified and field-tested for attraction of adults of D. minutus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae) . Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae). Our results are consistent with these findings, showing that aldehydes are attractive to insect target insects. Uechi et al showed that hexanal was not attractive to P.…”
Section: Discussionsupporting
confidence: 84%
“…Ukeh et al showed that a synthetic blend of hexanal, octanal, and (E)-2-heptanal identified from maize seed volatiles was significantly attractive to Sitophilus zeamais (Coleoptera: Curculionidae) . Similar studies have been reported on various insect species, for example, Triatoma infestans (Hemiptera: Reduviidae), Dinoderus minutus (Coleoptera: Bostrichidae), and Apis cerana (Hymenoptera: Apidae). Our results are consistent with these findings, showing that aldehydes are attractive to insect target insects. Uechi et al showed that hexanal was not attractive to P.…”
Section: Discussionsupporting
confidence: 84%
“…Although individual compounds can attract insects [ 19 ], mixtures of plant volatile components can enhance such attractive effects; Aglaomorpha histrio is trapped with a ternary mixture of eugenol, benzyl acetate, and phenylacetaldehyde as the bait approximately four times more than with phenylacetaldehyde alone [ 20 ]. Similar results have been found in Pseudoplusia includens and Dinoderus minutus [ 21 , 22 ]. Field experiments have confirmed that a combination of four volatiles (phenylacetaldehyde, benzyl acetate, 1-heptanol, and hexanal) significantly attracts C. medinalis adults, but the underlying molecular mechanism remained unclear.…”
Section: Introductionsupporting
confidence: 88%